BUDAYA ORGANISASI LEMBAGA PENDIDIKAN DALAM PERSPEKTIF ISLAM - Muhammad Arif Syihabuddin (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2019)
This article discusses organizational culture with a focus on studies on the organizational culture of Islamic perspective. The writing of this article is motivated by the existence of factors that can influence the culture of Islamic Education organizations. In addition, the author also wants to conduct a study of cultural relations with Islam, as well as how the culture of Islamic perspective. The method used by the authors in this article is to search for various relevant literature. The results of the studies conducted were: 1. some figures defined organizational culture as more philosophical, but there were also more operational ones; 2. There are three processes and stages in forming organizational culture; 3. There is a relationship between culture and Islam, the relationship is proof that Islam is the basis, principle, controller and direction, besides that Islam is a source of value in the development of culture; 4. Organizational culture in Islamic Education institutions refers to the value of togetherness, basic assumptions, and artifacts adopted by Islamic Education institutions, whether boarding schools, madrassas or Islamic Higher Education institutions.